2006
DOI: 10.1128/iai.00974-06
|View full text |Cite
|
Sign up to set email alerts
|

Discordance in the Effects ofYersinia pestison the Dendritic Cell Functions Manifested by Induction of Maturation and Paralysis of Migration

Abstract: The encounter between invading microorganisms and dendritic cells (DC) triggers a series of events which include uptake and degradation of the microorganism, induction of a maturation process, and enhancement of DC migration to the draining lymph nodes. Various pathogens have developed strategies to counteract these events as a measure to evade the host defense. In the present study we found that interaction of the Yersinia pestis EV76 strain with DC has no effect on cell viability and is characterized by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 68 publications
1
31
2
Order By: Relevance
“…While less is known about YopJ's effect on DC, YopP in Y. enterocolitica infection of fully differentiated DC has been implicated in mediating apoptosis (in murine DC), suppressing cytokine production, antigen presentation and immunostimulatory capacity [14,17,18]. In Y. pestis, YopJ appears to have less of a negative effect on the survival and immune function of differentiated murine DC, but rather has a marked effect on DC migration [19]. Our findings suggest that YopJ can also inhibit DC immunogenicity upstream of the mature DC, namely by disrupting signaling pathways during progenitor to DC differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While less is known about YopJ's effect on DC, YopP in Y. enterocolitica infection of fully differentiated DC has been implicated in mediating apoptosis (in murine DC), suppressing cytokine production, antigen presentation and immunostimulatory capacity [14,17,18]. In Y. pestis, YopJ appears to have less of a negative effect on the survival and immune function of differentiated murine DC, but rather has a marked effect on DC migration [19]. Our findings suggest that YopJ can also inhibit DC immunogenicity upstream of the mature DC, namely by disrupting signaling pathways during progenitor to DC differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…An important caveat is that our studies were not designed to rigorously characterize YopJ-mediated apoptosis. Interestingly, however, it has been recently suggested that YopJmediated killing of DC is a much less prominent feature of Y. pestis than seen for Y. enterocolitica [19] or Y. pseudotuberculosis [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCR7 has long been thought to be the dominant mediator of DC migration. However, a study by Velan et al (36) showed that DCs pulsed with Yersinia pestis showed decreased migration toward CCL19 in an in vitro and an in vivo assay but still showed upregulated CCR7 expression. In a study on the role of CD47 in DC migration, CD47 2/2 DCs showed normal CCR7 expression but impaired migration to CCL19 in an vitro assay (37).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that Y. pestis selectively engages Ms, DCs, and PMNs for Yop injection through the T3SS (34), and the migration of DCs to draining lymph nodes is inhibited when the infecting Y. pestis strain contains the virulence plasmid carrying genes encoding Yops (63). We monitored the numbers of three major subgroups of DCs in mice infected by the parent or YopM Ϫ Y. pestis.…”
Section: Discussionmentioning
confidence: 99%